Pulmonary Tuberculosis CT-Scan Features and Sputum Smear in Tertiary Referral Hospital - Nur Amelia Bachtiar; Sri Asriyani; Bachtiar Murtala; Irawaty Djaharuddin; Andi Alfian Zainuddin; Nikmatia Latief (Faculty of Medicine, Hasanuddin University., 2020)
Introduction: Management of pulmonary tuberculosis (PTB) from primary and secondary health centers might affect the result of sputum acid-fast bacilli (AFB) smear and features of lung computed tomography scan (CT-scan) presented in tertiary hospitals. The study aims to investigate comparison between CT-scan features of PTB with sputum AFB smear in Wahidin Sudirohusodo Hospital as the top referral hospital in the Eastern part of Indonesia. Methods: This is a retrospective study of patients diagnosed as PTB by pulmonologist of nine months period. Patients with available CT-scan and sputum AFB smear results are included in the study. CT-scan features re-evaluated with RadiAnt DICOM viewer for standardized reading. The relationship between data obtained was analyzed with a chi-square test. Results: Sixty-one PTB patients were entered into the study. The three most common features found in CT were consolidation (93.4%) followed by Tree-in-bud (91.8%), and fibrosis calcification (85.2%). Relationship of CT features and sputum AFB smear was significant on cavity (p-value: 0.002) and pleural effusion (p-value: 0.020). However, unlike cavity (OR = 1.667), pleural effusion has opposite relationship (OR = 0.205) with sputum AFB smear. Conclusions: Pulmonary tuberculosis CT features seen in top referral hospitals can be very severe with consolidation and tree-in-buds as the most common features found in more than 90% of the cases. Feature of cavity may help radiologist to distinct highly active PTB with positive sputum AFB smear while presence of pleural effusion should raise the suspicion from pulmonologists to add further laboratory investigation.